2023
DOI: 10.1002/adom.202301949
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering for Highly Efficient and Stable Perovskite Solar Cells

Chenxu Zhao,
Hong Zhang,
Anurag Krishna
et al.

Abstract: The ongoing global research and development efforts on perovskite solar cells (PSCs) have led the power conversion efficiency to a high record of 26.1%. The optimization of PSC processing methods, the development of new compositions, and the introduction of passivation strategies are key factors behind the meteoric rise in performance. In particular, defect passivation and mitigation of ion migration via molecular engineering of the interfaces have played a critical role in enhancing the photovoltaic performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 175 publications
0
4
0
Order By: Relevance
“…Research has shown that the perovskite BIF is key to limiting the quality of perovskite thin films and the efficiency of devices [53]. Due to continuous solution and temperature erosion, the bottom surface of the perovskite is more prone to interface defects than the body surface and upper surface of the perovskite [54]. Therefore, by modifying the BIF, the crystalline growth of the perovskite can be controlled, light-generated carriers can be extracted, and band energy can be adjusted for energy matching.…”
Section: Interface Modificationmentioning
confidence: 99%
“…Research has shown that the perovskite BIF is key to limiting the quality of perovskite thin films and the efficiency of devices [53]. Due to continuous solution and temperature erosion, the bottom surface of the perovskite is more prone to interface defects than the body surface and upper surface of the perovskite [54]. Therefore, by modifying the BIF, the crystalline growth of the perovskite can be controlled, light-generated carriers can be extracted, and band energy can be adjusted for energy matching.…”
Section: Interface Modificationmentioning
confidence: 99%
“…[52] The multifunctional molecular bridges (especially organic halides) constitute the other significant class of materials employed for passivating the ETL/CsPbX 3 interface. [53] Typically, halogen, carboxylic acid group (-COOH) or amine group (-NH 2 ) within these molecules establish robust interactions with TiO 2 and perovskite layer, thereby enhancing the efficient electron transport from the perovskite to TiO 2 ETL. For instance, Liu et al utilized 5-amino-2,4,6-triiodoisophthalic acid (ATPA) as a multifunctional molecule, which anchored onto both TiO 2 and CsPbI 3 through the reaction with hydroxyl groups (-OH), which were dangling on the TiO 2 , and passivated defects in perovskite films.…”
Section: Interface Regulation Between the Etl And The Perovskite Layermentioning
confidence: 99%
“…[10][11][12][13][14][15] Interface modification strategies are currently one of the most widely studied and effective methods to reduce the defect density inside the PSCs. 16,17 Various types of passivating molecules with different chemical structures have been designed to target different types of defects at the interface, such as 4hydroxypicolinic acid (4HPA), 18 N-(2-pyridyl)pivalamide (NPP), 19 self-crosslinked fluorosilicone polymer gel, 20 octylamine (OA) functionalized with sulfanilic acid (OAS), p-toluenesulfonic acid (OAT), camphorsulfonic acid (OAC), 21 and so on. However, due to the singularity of organic passivation molecules, improvements in both efficiency and stability remain limited.…”
Section: Introductionmentioning
confidence: 99%